Analogy conference of birds by Attar - Ramzan, Nadia (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This research article explores the profound analogy presented in the novel "The Conference of the Birds" by Attar, a Persian Sufi poet and mystic. The study aims to delve into the allegorical narrative structure and symbolic elements employed in the novel to depict a spiritual journey and quest for self-realization. By analyzing the philosophical implications and insights embedded within Attar's work, this research contributes to a deeper understanding of the novel's relevance in exploring human existence and the pursuit of spiritual enlightenment.